psychology-cognition 2018
DOI: 10.35841/psychology-cognition.3.1.16-28
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the Tomatis® Method on self-regulation in a sample of South African university students.

Abstract: Aim: To evaluate the extent to which the Tomatis ® Method improves self-regulation in a sample of South African university students (N=49). Method: A concurrent, mixed method approach using a three-group pre-post, and repeated postassessment design, was used. Results: The Tomatis ® Method had a positive impact on hyporesponsiveness in the left ear and spatialization of the right ear, on introjected regulation and perseverance, as well as on psychological and social well-being. Benefits were also qualitatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The teaching interactions in language courses have demonstrated that the philologist can understand and intervene in the reading difficulties of students with Attention Deficit Disorder with or without Hyperactivity Disorder (ADHD), according to the definitions and bibliographic documentation given for perceptual reading (Avramidis and Norwich, 2015), the reading (Bonthuys et al 2018) and the addiction with the Internet games.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The teaching interactions in language courses have demonstrated that the philologist can understand and intervene in the reading difficulties of students with Attention Deficit Disorder with or without Hyperactivity Disorder (ADHD), according to the definitions and bibliographic documentation given for perceptual reading (Avramidis and Norwich, 2015), the reading (Bonthuys et al 2018) and the addiction with the Internet games.…”
Section: Resultsmentioning
confidence: 99%
“…The philologist can understand the relationship between specific reading difficulties and ADHD, according the perceptual reading (Bonthuys et al 2018) and surface reading. Also, he will be able to make a positive contribution to controlling behavioral problems from online addiction.…”
Section: H1mentioning
confidence: 99%